Size and value risk in financial firms - Baek, Seungho; Bilson, John F.O. (Journal of Banking & Finance, 2015)
The Fama and Frenchs three factor model (Fama and French, 1992, Fama and French, 1993) is now the most popular replacement for CAPM. In the model, the fact that the model excludes financial firms is significant because financial firms are a large fraction of the value of the U.S. stock market. Also, there is no theoretical reason for excluding financial firms. Modigliani and Miller, 1958, Modigliani and Miller, 1963 suggest that leverage affects beta, but it does not invalidate the capital asset pricing model. It would therefore be more satisfying if the pricing model applied generally, rather than being restricted to non-financial corporations. Thus, we assess the validity of size and value risk as common risk factors to measure of the cross-section of expected stock returns in financial companies. Empirical asset pricing tests suggest two findings. First, size and value risk premia commonly exists in both nonfinancial and financial firms, even if two factors are less explicable in financial firms. Second, an interest rate risk premium (ΔL/L) which defined as a financial firm specific risk factor only appears in financial companies.